Production of metal powders by gas atomization using swirl and non-swirl nozzles - Kazuki YOSHIMURA; Kazuya SAITO (Nihon Kikai Gakkai ronbunshu, 2022)
Gas atomization, in which high-pressure gas jet impinges on molten metal stream from the melt tube to atomize it, is a popular method of producing fine metal powders. In this study, we focused on a swirling flow of the injection gas as a factor affecting the produced powder. Computational analyses and experiments were carried out to investigate the effect of the swirling gas flow on the atomization process. First, a single-phase flow analysis was performed considering only the injection gas. The simulated aspiration pressure agreed well with the experimental results. The behavior of the aspiration pressure against the gas injection pressure depended on the presence of the swirling flow. The simulation results clarified that the aspiration pressure was decreased by backflow into the melt tube in the case of the non-swirl nozzle. The backflow was caused by a vortex just below the melt tube tip, which was generated by the injected gas. On the other hand, in case of the swirl nozzle, the swirling flow decreased the pressure at the center of gas flow and inside the melt tube, which caused a high and stable aspiration pressure. Next, the effect of the swirling flow on the melt behavior and particle atomization was investigated numerically. A low-velocity region was generated at the center of the gas flow as a result of the mass loading of the melt, which was larger in the swirl nozzle. Consequently, the particles in the swirl nozzle were coarser than those in the non-swirl nozzle because some of the particles flying in the low-velocity region could not be atomized enough. Finally, metal powders were produced using a gas atomization plant, and the powder sizes and the surface images were compared. The powder size distribution showed that the non-swirl nozzle produced finer powders than the swirl nozzle did, as in the simulation results.